Listening Teaching Strategies in Online Learning - Tarigan, Adinda Maharani; Pohan, Ikhwan (English Education:Journal of English Teaching and Research, 2022)
This study discusses Listening Teaching Strategies in Online Learning. The reason the researcher chose this discussion is that listening is one of the important points in English, where teachers need important strategies to convey every material in listening learning, both directly and through online learning. The researcher's aim in this study was to understand listening teaching strategies in online learning, and the collection method chosen by the researchers in this study was qualitative because the researchers collected data directly through questionnaires given to respondents. All the information that the researchers obtained in this study came from respondents, namely 10 English teachers who teach in junior high schools and have experience teaching listening material to students, either directly or through online learning. The data researcher obtained in this study was sourced from respondents' answers, in this study the researchers discussed in detail and accurately related to Listening Teaching Strategies in Online Learning that can be proven true. Keywords: Online Learning; Listening; Teaching Strategies